USULAN PERANCANGAN SISTEM PENERANGAN PADA NEW LINE 2B ASSEMBLING UNIT PT ASTRA HONDA MOTOR - Dory, Frans; Aribowo, Budi (Industrial and Systems Engineering Assessment Journal (INASEA), 2006)
One of important factor to design line assembling is by designing lightning system design and the system will effect on the quality of the operator performance. Therefor, it need to design a lightning that will be used in new line 2B assembling unit of Astra Honda Motor company.